Coinfection of Herpes Simplex virus 2 and Mycobacterium chelonae in acute hydrops associated with keratoconus: A case report - Pedro Marques-Couto; Ana Gama-Castro; Teresa Carvalho; Rodrigo Vilares-Morgado; João Pinheiro-Costa; Dolores Pinheiro; Ana Maria Cunha (IDCases)
Purpose: Acute hydrops is a characteristic complication of corneal ectatic diseases. While Mycobacterium chelonae is known to cause various ophthalmic infections, most commonly following surgery, there are no reported cases of infection by this microorganism in the context of acute hydrops, nor concurrent with Herpes Simplex virus 2 infection. Observations: A 33-year-old Portuguese woman of Caucasian ethnicity with a history of keratoconus presented with a red eye and ocular discomfort in the right eye at the Ophthalmology Emergency Department. Initial examination revealed acute hydrops with no epithelial defects nor signs of infection. Posteriorly, she developed dendritic epithelial lesions suggestive of Herpes Simplex virus infection. These lesions progressed, leading to a central corneal infiltrate and descemetocele. Due to perforation of the descemetocele, a tectonic penetrating keratoplasty was successfully performed, and coinfection of Herpes Simplex virus 2 and Mycobacterium chelonae was later confirmed through microbiological examination. Conclusions and importance: This is the first reported case of corneal coinfection with Herpes Simplex virus 2 and Mycobacterium chelonae in the setting of acute hydrops. The combination of corneal edema, previous viral infection, and prolonged corticosteroid use likely created a “perfect storm” scenario, predisposing the patient to this unusual coinfection. Our findings highlight the need for heightened awareness of atypical infections in patients with acute hydrops and suggest that such complications may alter corneal barrier function. This case contributes to the understanding of complex interactions between corneal conditions and microbial infections.